Robotic navigation in spine surgery: Where are we now and where are we going?. (December 2021) - Wang, Timothy Y.; Park, Christine; Dalton, Tara; Rajkumar, Shashank; McCray, Edwin; Owolo, Edwin; Than, Khoi D.; Abd-El-Barr, Muhammad M.
Highlights: Robotics is being increasingly used in minimally invasive spine surgery. New applications of robots other than pedicle screw placement are emerging. Use of robots entails a learning curve but may increase surgical efficiency. Cost effectiveness of robots remains unclear. Abstract: Robotic navigation is a new and rapidly emerging niche within minimally invasive spine surgery. The robotic arms-race began in 2004 and has resulted in no less than four major robotic surgical adjuncts. Current Food and Drug Administration (FDA)-approved applications of robotic navigation are limited to pedicle screw instrumentation, but new indications and experimental applications are rapidly emerging. As with any new technology, robotic navigation must be vetted for clinical efficacy, efficiency, safety, and cost-effectiveness. Given the rapid advancements made on a yearly basis, it is important to make frequent and objective assessments of the available technology. Thus, the authors seek to provide the most up-to-date review of the history, currently available technology, learning curve, novel applications, and cost effectiveness of today's available robotic systems as it relates to spine surgery.